Membangun Kepercayaan Konsumen: Live Streaming dan Real Picture Product sebagai Kunci Menuju Konversi Penjualan - Ade Farin; Tsabitah Rahmahdiyyah; Nurul Lailiyah; Yolanda Irma Zunita; Bella May Ranti Putri; Rizal Idul Fitrianto; Alfath Fabian Adinata; Afifatus Sholichah (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul UlamaNusa Tenggara Barat, 2025)
The aim of this research is to find out whether live streaming and real product pictures can build consumer trust and can be the key to sales conversion. The research method used is quantitative and for data collection using a questionnaire and the data analysis technique in this research uses PLS. Conclusions describe the answer to the hypothesis and/or research objectives or scientific findings obtained. The conclusion does not contain a repetition of the results and discussion, but rather a summary of the findings as expected in the objective or hypothesis.